High-purity yttrium oxide transparent ceramic and preparation method thereof
By using a double-layer four-oblique blade stirring rod to absorb iron impurities during the preparation process of yttrium oxide ceramics, combined with the solid-state reaction method, the problem of iron impurities in yttrium oxide ceramics was solved, and yttrium oxide transparent ceramics with high optical quality and efficient production were achieved .
Patent Information
- Application Number
- CN202411477221.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
AI Technical Summary
The existing preparation method of yttrium oxide transparent ceramics is limited by the iron impurities and activity problems in yttrium oxide nanopowders, and it is difficult to prepare yttrium oxide transparent ceramics with high optical quality.
The double -layer four -diagonal leaf type and magnetic adsorption mixing rod is mixed with pulp after the ball grinding, combined with the fixation of the reactor -based oxidation and transparent ceramics to effectively avoid the appearance of impurities iron points.
It achieves the acquisition of high-purity, high-optical-quality yttrium oxide transparent ceramics, improves production efficiency and reduces ball milling time.
Smart Images

Figure CN119350027A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic materials, and in particular to a high-purity yttrium oxide transparent ceramic and a preparation method thereof. Background Art
[0002] Due to the uncontrollability of the upstream raw material powder, brown dot-like iron impurities can be observed in yttrium oxide ceramics, affecting product quality. Iron spots are usually eliminated by cutting and surface grinding and polishing, which easily causes waste of materials and does not fundamentally solve this problem. In addition, in order to prepare yttrium oxide transparent ceramics with high optical quality, it is first necessary to prepare high-activity, high-purity yttrium oxide nanopowders. Liquid phase methods are currently widely used, including precipitation methods and combustion methods, but the yield of yttrium oxide nanopowders obtained by this method is very low, and there is no prospect of realizing mass production, and it is difficult to meet the production needs of large-size ceramics. Although the yttrium oxide nanopowders prepared by the traditional solid phase method have the advantage of high production efficiency, they are still limited by the influence of powder purity (mainly iron impurities) and activity, and it is difficult to prepare yttrium oxide transparent ceramics with high optical quality.
[0003] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a high-purity yttrium oxide transparent ceramic and a preparation method thereof, aiming to solve the problem that the existing preparation method of yttrium oxide transparent ceramic is limited by the influence of iron impurities and activity of yttrium oxide nanopowder, and it is difficult to prepare yttrium oxide transparent ceramic with high optical quality.
[0005] The technical solution of the present invention is as follows:
[0006] A first aspect of the present invention provides a method for preparing a high-purity yttrium oxide transparent ceramic, comprising the steps of:
[0007] placing yttrium oxide powder, a sintering aid and a solvent in a ball milling device containing a ball milling medium for ball milling to obtain a ball milled slurry;
[0008] The ball-milled slurry is stirred using a double-layer four-slant-blade stirring rod with a magnetic adsorption function to obtain a stirred slurry;
[0009] The stirred slurry is dried and sieved in sequence to obtain yttrium oxide nanopowder;
[0010] The yttrium oxide nanopowder is sequentially calcined, molded, sintered, annealed and processed to obtain yttrium oxide transparent ceramics.
[0011] Optionally, the sintering aid is a zirconium oxide sintering aid, the ball milling medium is a zirconium oxide ball, and the solvent is anhydrous ethanol.
[0012] Optionally, the mass ratio of the yttrium oxide powder to the sintering aid is 200:1-200:12.
[0013] Optionally, the ball milling speed is 200-250 r / min, and the ball milling time is 30-36 h.
[0014] Optionally, the stirring speed is 400-450 r / min, and the stirring time is 0.5-2 h.
[0015] Optionally, the drying temperature is 60-80° C. and the drying time is 12-24 hours.
[0016] Optionally, the average grain size of the yttrium oxide transparent ceramic is 5-7 μm.
[0017] A second aspect of the present invention provides a high-purity yttrium oxide transparent ceramic, wherein the high-purity yttrium oxide transparent ceramic is prepared by the preparation method of the high-purity yttrium oxide transparent ceramic described in the present invention.
[0018] Beneficial effect: The present invention adopts a solid phase reaction method to prepare yttrium oxide transparent ceramics. The main improvement is to use a double-layer four-slanted blade stirring rod with magnetic adsorption to stir the slurry after ball milling, so as to effectively avoid the appearance of impurity iron points in the finished yttrium oxide ceramics, thereby obtaining yttrium oxide transparent ceramics with high optical quality. At the same time, the double-layer four-slanted blade can form an axial flow fluid field to the greatest extent, with shearing, crushing and dispersion effects, which can reduce the ball milling time and improve production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a schematic diagram of the present invention using a double-layer four-slant-blade stirring rod with magnetic adsorption to stir the ball-milled slurry.
[0020] Figure 2 This is a particle size diagram of the yttrium oxide nanopowder prepared in Comparative Example 1.
[0021] Figure 3 This is the EDS image of the yttrium oxide nanopowder prepared in Comparative Example 1.
[0022] Figure 4 This is a physical picture of the yttrium oxide transparent ceramic prepared in Comparative Example 1.
[0023] Figure 5 This is a diagram showing the particle size of the yttrium oxide nanopowder prepared in Example 1.
[0024] Figure 6This is a cross-sectional SEM image of the finished yttrium oxide transparent ceramic product prepared in Example 1.
[0025] Figure 7 This is the transmittance spectrum of the yttrium oxide transparent ceramic product prepared in Example 1.
[0026] Figure 8 This is the transmittance spectrum of the yttrium oxide transparent ceramic product prepared in Example 2.
[0027] Fig. 9 This is the transmittance spectrum of the yttrium oxide transparent ceramic product prepared in Example 3.
[0028] Fig.10 This is a physical picture of the yttrium oxide transparent ceramic prepared in Example 3.
[0029] Fig.11 This is the grain size distribution diagram of the yttrium oxide transparent ceramic prepared in Example 3. DETAILED DESCRIPTION
[0030] The present invention provides a high-purity yttrium oxide transparent ceramic and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0031] Brown spot-like iron impurities can be observed in existing yttrium oxide ceramics, which affects product quality. Usually, the iron spots are removed by cutting and surface grinding and polishing, but this problem is not fundamentally solved.
[0032] Based on this, an embodiment of the present invention provides a method for preparing a high-purity yttrium oxide transparent ceramic, which comprises the steps of:
[0033] placing yttrium oxide powder, a sintering aid and a solvent in a ball milling device containing a ball milling medium for ball milling to obtain a ball milled slurry;
[0034] The ball-milled slurry is stirred using a double-layer four-slant-blade stirring rod with a magnetic adsorption function to obtain a stirred slurry;
[0035] The stirred slurry is dried and sieved in sequence to obtain yttrium oxide nanopowder;
[0036] The yttrium oxide nanopowder is sequentially calcined, molded, sintered, annealed and processed to obtain yttrium oxide transparent ceramics.
[0037] The embodiment of the present invention uses a double-layer four-slant blade stirring rod with magnetic adsorption (also referred to as a double-layer four-slant blade magnetic rod with strong adsorption capacity) to stir the slurry after ball milling. The stirring rod can adsorb iron impurities, thereby effectively avoiding the appearance of impurity iron points in the finished yttrium oxide ceramics, and obtaining yttrium oxide transparent ceramics with high optical quality. At the same time, the double-layer four-slant blade can form an axial flow fluid field to the greatest extent, which has shearing, crushing and dispersing effects on the powder after ball milling, breaking the soft agglomeration inside the powder, reducing the average particle size of the yttrium oxide powder, and thus improving the sintering activity of the powder. At the same time, the ball milling time can be reduced and production efficiency can be improved.
[0038] In the prior art, when stirring is not performed, the ball milling time is usually 48 hours. The long ball milling process will inevitably cause the loss of ball milling media, resulting in changes in the chemical composition of the powder, and affecting the optical quality of the yttrium oxide ceramic. In the embodiment of the present invention, since a double-layer four-slant blade stirring rod with magnetic adsorption is used for stirring, the ball milling time only needs 30-36 hours, thereby reducing the ball milling time, improving production efficiency, and reducing the impact of ball milling on the optical quality of the yttrium oxide ceramic.
[0039] In one embodiment, the conditions for stirring the ball-milled slurry using a double-layer four-slant-blade stirring rod with magnetic adsorption include:
[0040] The main material of the stirring paddle is neodymium iron boron magnet;
[0041] The ratio of the diameter of the stirring blade to the diameter of the container (for containing the slurry after ball milling) is 0.2-0.5;
[0042] The inclination angle of the stirring blade to the horizontal plane is 30°-60°;
[0043] The ratio of the upper stirring paddle blade height (from the bottom of the container) to the slurry height (from the bottom of the container) is 0.6-0.8, and the ratio of the lower stirring paddle blade height (from the bottom of the container) to the slurry height (from the bottom of the container) is 0.1-0.3;
[0044] The ratio of the diameter of the stirring paddle to the diameter of the container is 0.15-0.2.
[0045] Through research and experiments, it is found that stirring under the above conditions can more effectively adsorb iron impurities, thereby avoiding the appearance of impurity iron points in the finished yttrium oxide ceramics, ensuring the acquisition of yttrium oxide transparent ceramics with high optical quality. At the same time, the shearing, crushing and dispersion effects can be improved.
[0046] In one embodiment, the sintering aid is a zirconia sintering aid or the like, but is not limited thereto.
[0047] In one embodiment, the ball milling medium is zirconia ball or the like, but is not limited thereto.
[0048] In one embodiment, the solvent is anhydrous ethanol, etc., but is not limited thereto.
[0049] In one embodiment, the mass ratio of the yttrium oxide powder to the sintering aid is 200:1-200:12, such as 200:1, 200:3, 200:5, 200:6, 200:7, 200:9, 200:11, 200:12, etc., but not limited thereto.
[0050] In one embodiment, the ball milling speed is 200-250 r / min, and the ball milling time is 30-36 h.
[0051] In one embodiment, the stirring speed is 400-450 r / min, and the stirring time is 0.5-2 h.
[0052] In one embodiment, the drying temperature is 60-80° C. and the drying time is 12-24 hours.
[0053] In one embodiment, the average grain size of the yttrium oxide transparent ceramic is 5-7 μm, such as 5.8 μm, 6.63 μm, etc.
[0054] A second aspect of the present invention provides a high-purity yttrium oxide transparent ceramic, wherein the high-purity yttrium oxide transparent ceramic is prepared by the preparation method of the high-purity yttrium oxide transparent ceramic described in the present invention.
[0055] The present invention is further described in detail below through several specific embodiments.
[0056] Example 1
[0057] Taking the preparation of 200g yttrium oxide nanopowder as an example, 194.32g of yttrium oxide powder with a purity of not less than 99.99% and 5.58g of zirconium oxide sintering aid are weighed. Zirconia balls with a diameter of 5mm are used as ball milling media and anhydrous ethanol is used as solvent. The weighed yttrium oxide powder and zirconium oxide sintering aid are placed in a zirconium oxide ball mill for planetary ball milling. The ball milling speed is 200r / min and the ball milling time is 30h. The ball-milled slurry is poured into a measuring cup, and a double-layer four-slant-blade stirring rod with magnetic adsorption is used to stir the ball-milled slurry. The stirring speed is 400r / min and the stirring time is 0.5h. The stirred slurry is then placed in an oven for drying at a drying temperature of 60°C for 12h. The dried powder is sieved to obtain yttrium oxide nanopowder.
[0058] The yttrium oxide nanopowder was then calcined in a muffle furnace at a calcination temperature of 900°C for 2 hours. The calcined powder was double-sided pressed into a 100×100mm square blank, at a pressure of 20MPa and a holding time of 1min. Then, cold isostatic pressing was performed, at a pressure of 200MPa and a holding time of 5min to obtain a yttrium oxide blank. The yttrium oxide blank was placed in a vacuum sintering furnace for vacuum sintering at a vacuum sintering temperature of 1750°C for 5 hours. Then, hot isostatic pressing was performed at a sintering temperature of 1500°C, a pressure of 198MPa, and a holding time of 2h. Then, annealing was performed at a temperature of 1200°C for 10 hours. Finally, double-sided polishing was performed to a thickness of 7mm to obtain yttrium oxide transparent ceramics.
[0059] Comparative Example 1
[0060] The method is basically the same as Example 1, except that the slurry after ball milling is not stirred but directly placed in an oven for drying.
[0061] Figure 2 This is a particle size diagram of the yttrium oxide nanopowder prepared in Comparative Example 1. It can be seen that the particle size distribution of the yttrium oxide nanopowder presents a bimodal distribution state, indicating that the powder is agglomerated; Figure 3 This is the EDS image of the yttrium oxide nanopowder prepared in Comparative Example 1, showing the presence of obvious Fe impurities; Figure 4 The yttrium oxide transparent ceramic prepared in Comparative Example 1 shows that there are many iron spots inside the sample, which seriously affect the optical quality.
[0062] Figure 5 This is a particle size diagram of the yttrium oxide nanopowder prepared in Example 1. At this time, it is a single-peak distribution, the agglomeration phenomenon disappears, the average particle size is about 200nm, and it has a high sintering activity; Figure 6 This is a cross-sectional SEM image of the finished yttrium oxide transparent ceramic product prepared in Example 1. No pores were observed, and the average grain size was about 5.8 μm. Figure 7 This is the transmittance spectrum of the 7 mm thick yttrium oxide transparent ceramic product in Example 1, and the infrared transmittance at 1100 nm is 77.6%.
[0063] Example 2
[0064] Taking the preparation of 200g yttrium oxide nanopowder as an example, 194.32g of yttrium oxide powder with a purity of not less than 99.99% and 5.58g of zirconium oxide sintering aid are weighed. Zirconia balls with a diameter of 5mm are used as ball milling media and anhydrous ethanol is used as solvent. The weighed yttrium oxide powder and zirconium oxide sintering aid are placed in a zirconium oxide ball mill for planetary ball milling. The ball milling speed is 250r / min and the ball milling time is 36h. The ball-milled slurry is poured into a measuring cup, and a double-layer four-slant-blade stirring rod with magnetic adsorption is used to stir the ball-milled slurry. The stirring speed is 430r / min and the stirring time is 1h. The stirred slurry is then placed in an oven for drying at a drying temperature of 70°C for 18h. The dried powder is sieved to obtain yttrium oxide nanopowder.
[0065] The yttrium oxide nanopowder was then calcined in a muffle furnace at a calcination temperature of 1000°C for 2.5 hours. The calcined powder was double-sided press-formed into a 100×100mm square blank, at a pressure of 15MPa and a holding time of 2min. Then, cold isostatic pressing was performed, at a pressure of 200MPa and a holding time of 5min to obtain a yttrium oxide blank. The yttrium oxide blank was placed in a vacuum sintering furnace for vacuum sintering at a vacuum sintering temperature of 1800°C and a holding time of 8h. Then, hot isostatic pressing was performed at a sintering temperature of 1600°C, a pressure of 198MPa, and a holding time of 2.5h. Then, annealing was performed at a temperature of 1300°C for 12h. Finally, double-sided polishing was performed to a thickness of 7mm to obtain yttrium oxide transparent ceramics.
[0066] Figure 8 This is the transmittance spectrum of the 7 mm thick yttrium oxide transparent ceramic product prepared in this example. The infrared transmittance at 1100 nm is 80.7%, which is close to the theoretical value.
[0067] Example 3
[0068] Taking the preparation of 200g yttrium oxide nanopowder as an example, 194.32g of yttrium oxide powder with a purity of not less than 99.99% and 5.58g of zirconium oxide sintering aid are weighed. Zirconia balls with a diameter of 5mm are used as ball milling media and anhydrous ethanol is used as solvent. The weighed yttrium oxide powder and zirconium oxide sintering aid are placed in a zirconium oxide ball mill for planetary ball milling. The ball milling speed is 220r / min and the ball milling time is 36h. The ball-milled slurry is poured into a measuring cup, and a double-layer four-slant-blade stirring rod with magnetic adsorption is used to stir the ball-milled slurry. The stirring speed is 450r / min and the stirring time is 2h. The stirred slurry is then placed in an oven for drying at a drying temperature of 80°C for 24h. The dried powder is sieved to obtain yttrium oxide nanopowder.
[0069] The yttrium oxide nanopowder was then calcined in a muffle furnace at a calcination temperature of 1100°C for 3 hours. The calcined powder was double-sided press-formed into a 100×100mm square blank, at a pressure of 25MPa and a holding time of 3min. Then, cold isostatic pressing was performed, at a pressure of 200MPa and a holding time of 5min to obtain a yttrium oxide blank. The yttrium oxide blank was placed in a vacuum sintering furnace for vacuum sintering at a vacuum sintering temperature of 1830°C and a holding time of 10h. Then, hot isostatic pressing was performed at a sintering temperature of 1650°C, a pressure of 198MPa, and a holding time of 2.5h. Then, annealing was performed at a temperature of 1400°C for 18h. Finally, double-sided polishing was performed to a thickness of 7mm to obtain yttrium oxide transparent ceramics.
[0070] Fig. 9 This is the transmittance spectrum of the 7 mm thick yttrium oxide transparent ceramic product prepared in this example. The infrared transmittance at 1100 nm is 81.7%, which is close to the theoretical value. Fig.10 Are there any impure iron spots in the actual picture of the finished yttrium oxide transparent ceramic product shown? Fig.11 This is the grain size distribution diagram of the yttrium oxide transparent ceramic prepared in this example, and the average grain size is 6.63 μm.
[0071] In summary, the present invention provides a high-purity yttrium oxide transparent ceramic and a preparation method thereof. The present invention adopts a solid phase reaction method to prepare yttrium oxide transparent ceramic. The key is to use a double-layer four-slanted blade stirring rod with a magnetic adsorption effect to stir the slurry after ball milling to effectively avoid the appearance of impurity iron points in the finished yttrium oxide ceramic, thereby obtaining yttrium oxide transparent ceramic with high optical quality. At the same time, the double-layer four-slanted blade can form an axial flow fluid field to the greatest extent, with shearing, crushing and dispersion effects, which can reduce the ball milling time and improve production efficiency.
[0072] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing high-purity yttrium oxide transparent ceramics, characterized in that: Includes steps: placing yttrium oxide powder, a sintering aid and a solvent in a ball milling device containing a ball milling medium for ball milling to obtain a ball milled slurry; The ball-milled slurry is stirred using a double-layer four-slant-blade stirring rod with a magnetic adsorption function to obtain a stirred slurry; The stirred slurry is dried and sieved in sequence to obtain yttrium oxide nanopowder; The yttrium oxide nanopowder is sequentially calcined, molded, sintered, annealed and processed to obtain yttrium oxide transparent ceramics.
2. The method for preparing high-purity yttrium oxide transparent ceramic according to claim 1, characterized in that: The sintering aid is zirconium oxide sintering aid, the ball milling medium is zirconium oxide balls, and the solvent is anhydrous ethanol.
3. The method for preparing high-purity yttrium oxide transparent ceramic according to claim 1, characterized in that: The mass ratio of the yttrium oxide powder to the sintering aid is 200:1-200:
12.
4. The method for preparing high-purity yttrium oxide transparent ceramic according to claim 1, characterized in that: The ball mill has a rotation speed of 200-250 r / min and a ball milling time of 30-36 h.
5. The method for preparing high-purity yttrium oxide transparent ceramic according to claim 1, characterized in that: The stirring speed is 400-450r / min, and the stirring time is 0.5-2h.
6. The method for preparing high-purity yttrium oxide transparent ceramic according to claim 1, characterized in that: The drying temperature is 60-80° C. and the drying time is 12-24 hours.
7. The method for preparing high-purity yttrium oxide transparent ceramic according to claim 1, characterized in that: The average grain size of the yttrium oxide transparent ceramic is 5-7 μm.
8. A high-purity yttrium oxide transparent ceramic, characterized in that: The high-purity yttrium oxide transparent ceramic is prepared by the preparation method of any one of claims 1 to 7.
Citation Information
Patent Citations
Yttria sinter and member for plasma processor
CN102015577A
Yttria transparent ceramic preparation method
CN107540374A
Yttrium oxide transparent ceramic and preparation method thereof
CN117088696A
A mud filter equipment for ceramic manufacture
CN207694983U
Kaolin iron impurity removing device for ceramic production
CN211463514U